Pengaruh Content Marketing dan Influencer Marketing Terhadap Keputusan Pembelian Melalui Fomo (Fear of Missing Out) Sebagai Variabel Mediasi pada Produk Lozy Hijab: Studi pada Generasi Z di Kabupaten Purworejo - Rukhama Futarini; Murry Harmawan Saputra; Hubi Rahmat Andika (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The Muslim fashion industry in Indonesia, particularly the hijab sector, has experienced rapid growth alongside the increasing use of social media for digital marketing. Lozy Hijab utilizes content marketing and influencer marketing through TikTok and Instagram to attract consumers and encourage purchase decisions. This study aims to analyze the effects of Content Marketing and Influencer Marketing on Purchase Decisions, with Fear of Missing Out (FoMO) as a mediating variable. A quantitative approach was employed using data collected from 150 Generation Z respondents in Purworejo Regency through Likert-scale questionnaires. The data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with SmartPLS 4.1.1.6. The findings reveal that Content Marketing and Influencer Marketing positively and significantly influence both Purchase Decisions and FoMO. Furthermore, FoMO has a positive and significant effect on Purchase Decisions and significantly mediates the relationships between Content Marketing and Purchase Decisions, as well as between Influencer Marketing and Purchase Decisions. These findings indicate that effective digital marketing strategies supported by influencers can strengthen consumers' purchasing decisions by increasing FoMO among Generation Z.